Applying the Audio-Lingual Method to Improve EFL Learners’ Pronunciation: A Study from Tenth Graders at SMA Bala Keselamatan Palu - Reniasni Kamidi; Mukrim Mukrim; Hastini Hastini; Sudarkam R. Mertosono (Hasanuddin University, 2025)
This study aims to find out whether the Audio-lingual method is effective in improving students' pronunciation, particularly in word stress, among tenth-grade students of SMA Bala Keselamatan Palu. The research employed a quasi-experimental design involving 54 students, divided into an experimental group (n=25) and a control group (n=29) through total sampling technique. The experimental group was taught using the audio-lingual method, while the control group followed conventional methods. Data were collected using pre-tests and post-tests, and analyzed using the Mann-Whitney U test. The results showed that the experimental group achieved a higher mean post-test score (75.44) compared to the control group (61.69). Statistical analysis using SPSS version 26 showed a significance value (Asymp. Sig. 2-tailed) of 0.000, which is less than 0.05, indicating a statistically significant difference between the two groups. These results indicate that the Audio-Lingual Method is effective in improving students' pronunciation, specifically in mastering word stress in English.